Immunohistochemical Coexpression of Epithelial Cell Adhesion Molecule and Alpha-Fetoprotein in Hepatocellular Carcinoma - Leonardo do Prado Lima; Carla Jorge Machado; João Bernardo Sancio Rocha Rodrigues; Leonardo de Souza Vasconcellos; Eduardo Paulino Junior; Paula Vieira Teixeira Vidigal; Vivian Resende (Canadian Journal of Gastroenterology and Hepatology)
Background and Aim. The epithelial cell adhesion molecule (EpCAM) has been proposed as a marker for cancer stem cells in human hepatocellular carcinoma (HCC) as well as in the development of novel target therapies. This study aimed to investigate the immunohistochemical expression of EpCAM and alpha-fetoprotein (AFP) in HCC patients and their association with clinicopathological characteristics. Methods. This study included Child-Pugh A HCC patients undergoing curative surgical resection. Results. A significant difference was observed in the ratio between the different phenotypes (p = 0.002), identifying 12 (29.3%) EPCAM positive tumors and 29 (70.7%) negative tumors. EpCAM+ expression was associated with AFP + (OR = 12.5, 95% CI, 1.9-84.1, p<0.001). In univariate analysis, a significant association was observed between AFP+ and EPCAM+ and the serum AFP level. A diameter of ≤ 5 cm was associated with EPCAM+, while angiolymphatic invasion was associated with APF+. In a multivariate analysis, only tumors of ≤ 5 cm were significantly associated with EpCAM+ (OR = 8.7; 95%CI, 1.27-100.0; p = 0.022). The overall survival rate was 74.9%, 69.4%, 69.4%, and 53.5% at 12, 24, 36, and 48 months, respectively. Conclusion. A considerable number of patients with EpCAM+ HCC would benefit from a specific target therapy.